Daoismo tropical: transplantação do Daoismo ao Brasil através da Sociedade Taoísta do Brasil e da Sociedade Taoísta SP - Costa, Matheus Oliva da (2015)
Daoism is a religion of Chinese origins that since the 19th century started to have contact with the Brazilian culture, beneath the Orientalism force. Since the second half of the 20th century, we see a second wave of Daoism spread, albeit indirectly. In the 1970s the Wǔ family Wu Jyh Cherng within them (Wǔ Zhìchéng) migrates from Taiwan to Rio de Janeiro, Brazil. In the 1990s, this Taiwanese naturalized Brazilian priest of the Celestial Masters Way founded the Daoist Society of Brazil (Sociedade Taoísta do Brasil - STB) along Brazilians, and later the Daoist Society in São Paulo (Sociedade Taoísta SP - ST-SP), which is our object of study. The goal here was to analyze the Daoism transplant process in Brazil through the STB and ST-SP. In addition to a systematization of the authors regarding the transplantation of religions theory, we were based on the theory of cultural hybridization, and a set of interpreters of Brazilian culture and Brazilian religion. We created the central hypothesis that in the STB and ST-SP the Daoism would be increasingly a hybrid result of the Brazilian religious matrix and an ideal model of Daoist linked to China. Methodologically, we conducted an extensive and constant literature review, and we refer to primary printed sources, virtual and audiovisual sources, participatory research, semi-structured interviews and informal conversations. With these data, we performed an analysis using the theoretical framework, which allowed us to confirm the central hypothesis. We also wove systematic contributions on: the presence and the type of Daoism entry in Brazil, identification of socio-historical phases of STB and ST-SP, and several observations about the process and results of transplantation of this Daoist group, such as the accommodation of the Brazilian religious demands on the liturgical rituals of these institutions